Writing connections as a source of significance: group poetry therapy among patients with advanced cancer - Nyfors, Mervi; Pöyhiä, Reino; Vehviläinen, Anna-Riikka; Lamminmäki, Annamarja (Journal of poetry therapy, 2025)
The need for psychosocial support in cancer treatment, especially in the palliative care phase, has been identified in a nationwide population-based study, published in BMC palliative care (Wang et al., 2016). This study discusses the use of group poetry therapy among patients with advanced cancer to address their psychosocial and emotional needs. A group of seven patients with advanced cancer used poetry therapeutic methods to examine the emotions provoked by a serious illness. The integrative poetry therapy method employed in this research aimed to reduce emotional loneliness, strengthen patient-experienced connectedness to self, others, and nature, and make these connections visible through writing and narration. This qualitative analysis examines the themes raised in the patients' texts from a connectivity-building viewpoint. Nature-themed metaphor and mindfulness work helped patients verbalize connectedness with others, nature, themselves, and their own individual resources and vulnerabilities. The group dealt with both constructive and destructive emotions. Emotions that strengthened and maintained connections included love, hope, and gratitude. These emotions were perceived as supportive and cherishable. Emotional writing provided a controlled and safe means to connect with destructive emotions, such as existential loneliness and abandonment.